Sculptors of cerebellar fissures and their potential as therapeutic targets for cerebellar dysfunction - Shen, Chiu-Lun; Tsai, Yu-Young; Tarn, Woan-Yuh (Frontiers in Cellular Neuroscience, 2025)
The cerebellum plays an important role in both motor control and cognition. The cerebellar cortex is neuron-rich and composed of characteristic folia and fissures. Defective cerebellar development leads to movement disorders and developmental delay. During early morphogenesis, cellular signaling programs orchestrate simultaneous cerebellar growth and foliation. Aberrant signaling causes various degrees of cerebellar hypoplasia. Based on mouse genetic studies, we discuss several developmental signaling pathways that drive cerebellar morphogenesis. Notably, hypoplasia of vermal lobules VI-VII has been linked to autism spectrum disorder and is in part attributed to brain-derived neurotrophic factor (BDNF)/tropomyosin receptor kinase B signaling. This review also discusses how BDNF biogenesis is critical for cerebellar foliation and whether restoring BDNF signaling could reverse cerebellar developmental disorders.